Double-balloon Enteroscopy, in the diagnosis and management of GI tract diseases at a tertiary level hospital. (Bangladesh Journal of Medicine, 2024)
Background: Double balloon Enteroscopy (DBE) is a newer endoscopic technique for examining the small bowel.  The aim of the study was to evaluate the indication, diagnostic and therapeutic impact of DBE in patients with suspected small bowel disease among adult population of Bangladesh. Methods: A descriptive, cross-sectional study was conducted on all patients above 18 years of age admitted for DBE examination under Department of Gastroenterology, Shaheed Suhrawardy Medical College Hospital, from January 2021 to December 2021.Results:The study respondents consisted of 80 patients, among them 68.75% male and 31.25% female, mean age 40.8 ± 14.7years. DBE procedures (antegrade route) were performed in 80 patients. Indications for DBE were Chronic Diarrhea 20(25%), Chronic Abdominal pain 19(23.8%), Obscure GI bleeding 15(18.8%), Melaena 13(16.3%), Small bowel obstruction 7(8.8%), Abnormal Imaging 3(3.8%), Anemia 3(3.8%) etc. DBE findings were Ulceration 17(21.3%), Mucosal irregularity 5(6.3%), Growth 5(6.3%), Vascular ectasia 4(5%), GIST 2(2.5%), Features suggestive of Crohn’s disease 2 (2.5%), Polyp 1(1.3%) etc.Histological findings were Tuberculosis 6(7.5%), Adenocarcinoma 4(5%), Crohn’s disease 3(3.8%), GIST 2(2.5%), Lymphoma 2(2.5%), Malignant melanoma 1(1.3%), Polyp 1(1.3%), IPSID 1(1.3%), Non-specific ulcer 12(15%) etc. Polypectomy was performed in one patient. Diagnostic yields after DBE in chronic diarrhea, chronic abdominal pain, obscure GI bleeding, Melaena and Small bowel obstruction were 35%, 42%, 53.5% , 46% and 43% respectively. Conclusion:DBE is a newer technique of small bowel examination and potentially various endoscopic therapeutic intervention of small-intestinal lesions. It is safe, useful, and also provides a high clinical impact.Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 154-155